Environmental dynamism, hostility, and dynamic capabilities in medium-sized enterprises. (August 2017) - Frank, Hermann; Güttel, Wolfgang; Kessler, Alexander
Global crises, disruptive technologies, or business models, as well as increasing cost pressure constantly require firm responses to sustain competitive advantage. The dynamic capabilities (DC) approach addresses the firm's ability to innovate and to reconfigure in order to cope with a dynamic environment. In our study, we investigate the impact of environmental dynamics and hostility on DC in 120 Austrian medium-sized enterprises. Our quantitative analysis indicates a significant relation between environmental dynamism and DC of medium-sized enterprises: The higher environmental dynamism in the firm's environment is, the more prevailing and important are DC. We further reveal, in detail, that different DC in medium-sized enterprises are important when environmental dynamism and/or environmental hostility increase. In particular, searching, learning, and flexibility rise as a result of an increase in environmental dynamism. However, hostility in the firm's environment only has an impact on searching opportunities and threats. DC for process efficiency are important both in high velocity and in moderately dynamic markets. Finally, firms in high-velocity environments perform in an ambidextrous mode combining DC for exploration and exploitation concurrently.